Dr. Tung Duong — Deep Plane Facelift — Kuala Lumpur - Duong, Tung (DEEPPLANE™, 2026)
Surgeon profile record for Dr. Tung Duong, practicing in Kuala Lumpur, Malaysia. Tracked in the DEEPPLANE™ directory of listed deep plane facelift specialists. Published under CC-BY-4.0.
DPID-003346; accessed 2026-08-14; CC-BY-4.0
Keywords: deep plane facelift; facial plastic surgery; rhytidectomy; SMAS; malaysia; kuala lumpur